Management of supine hypertension in patients with neurogenic orthostatic hypotension: scientific statement of the American Autonomic Society, European Federation of Autonomic Societies, and the European Society of Hypertension. Issue 8 (August 2019) - Jordan, Jens; Fanciulli, Alessandra; Tank, Jens; Calandra-Buonaura, Giovanna; Cheshire, William P.; Cortelli, Pietro; Eschlboeck, Sabine; Grassi, Guido; Hilz, Max J.; Kaufmann, Horacio; Lahrmann, Heinz; Mancia, Giuseppe; et al.
Abstract : N/A: Supine hypertension commonly occurs in patients with neurogenic orthostatic hypotension due to autonomic failure. Supine hypertension promotes nocturnal sodium excretion and orthostatic hypotension, thus, interfering with quality of life. Perusal of the literature on essential hypertension and smaller scale investigations in autonomic failure patients also suggest that supine hypertension may predispose to cardiovascular and renal disease. These reasons provide a rationale for treating supine hypertension. Yet, treatment of supine hypertension, be it through nonpharmacological or pharmacological approaches, may exacerbate orthostatic hypotension when patients get up during the night. Fall-related complications may occur. More research is needed to define the magnitude of the deleterious effects of supine hypertension on cardiovascular, cerebrovascular, and renal morbidity and mortality. Integration of more precise cardiovascular risk assessment, efficacy, and safety data, and the prognosis of the underlying condition causing autonomic failure is required for individualized management recommendations.